Thai cuisine restaurant performance in the United Kingdom (UK): A SEM analysis - Supawan, Panadda; Sornsaruht, Puris; Pimdee, Paitoon (My University, 2019)
The United Kingdom's out-of-home (OOH) foodservice industry in 2019 is estimated to be worth over £56 billion, with Thai cuisine restaurants estimated to be over 1,600 in this U.K. service sector. As such, the authors set out to investigate which factors influenced a Thai restaurant's performance (PF) in the United Kingdom. An analysis was conducted on the six hypotheses interrelationships between a Thai cuisine restaurant's food safety and hygiene leadership (RFSHL), service capability (SC), competitive advantage (CA), and performance (PF). Initial analysis was conducted by the use of confirmatory factor analysis [CFA], followed by a structural equation model [SEM] path analysis using LISREL 9.1 of the study's four latent variables. From the audited questionnaire sample of 368 Thai restaurant entrepreneurs and managers, the factors affecting PF were RFSHL, SC, and CA, which total effect [TE] values of 0.77, 0.50 and 0.29, respectively. The results showed that all the model's variables influenced the performance (PF) of Thai restaurants operating in the U.K. as the combined influence of the factors (R2) was 59%. It must be also noted that data suggests that restaurant entrepreneurs must embrace technological change and the use of social media platforms along with smartphones to facilitate the UK consumers shift to convenience, takeaway, and home delivery. There is also the need to market Thai food as a healthy and delicious alternative to other foods and create in-restaurant 'ambiance'.
Keywords: Competitive advantage; England; Food safety; Hygiene; Service capability